Electro-optics handbook - Waynant, Ronald W.; Ediger, Marwood N. (McGraw-Hill handbooks, 2000)
A valuable "must-have" tool for electronic and optical engineers, this Handbook is the only single-volume, tell-it-all guide to the use of optical devices and light in electronics systems. Developed by a towering figure in the field, this manual familiarizes you with UV, VUV and X-Ray lasers; visible, solid-state, semiconductor and infrared gas lasers; FEL and ultrashort laser pulses; visible and infrared optical materials; infrared and imaging detectors; optical fibers and fiber optic sensors; holography; laser spectroscopy and photochemistry; high resolution lithography for optoelectronics; and much more.